Pilot evaluation of a personalized commercial program on weight loss, health outcomes, and quality of life. Issue 12 (16th August 2021) - Hales, Sarah B; Schulte, Erica M; Turner, Tonya F; Malcolm, Robert; Wojtanowski, Alexis C; Rethorst, Chad; Pinto, Angela M; Foster, Gary D; O'Neil, Patrick M
Abstract: WW is a validated behavioral weight management program that encourages healthy habits. WW developed a method of personalizing the SmartPoints® budget depending on dietary and lifestyle preferences, and participants were placed into one of three plans as a pilot evaluation of this new program. In this 6-month, single-arm pilot study, participants attended weekly workshops and used an app to monitor eating and physical activity. Baseline and 6-month assessments included weight, waist circumference, blood pressure, energy intake, cravings, happiness, health-related quality of life, hunger, and fullness. Of 145 adults assessed at baseline, 126 (87%) provided follow-up data. Pre–post changes showed significant reductions in body weight (7.39% ± 5.93%), calories consumed (24.79% ± 32.35%) and significant improvements in cravings, happiness, all SF-36 scales and hunger but not in fullness. Greater % weight loss was related to greater improvements in happiness ( r = .38, p < .001), general health perceptions ( r = .29, p = .001), and health change ( r = .31, p = .001), and greater reduction in role limitations due to personal or emotional problems ( r = .24, p = .01). Greater % reduction in caloric intake was associated with greater reductions in cravings ( r = .23, p = .01), as well as with greater improvements in happiness ( r = .23, p = .01), physical functioning ( r = .23, p = .01), and general health perceptions ( r = .23, p = .01). Participants in this modified program achieved significant weight loss, regardless of dietary plan, as well as improvements in a variety of other physical and psychological constructs. Those who achieved greater reductions in weight also reported greater improvements in cravings, happiness and some quality of life measures. Abstract : Personalized commercial weight loss programs may be effective for weight loss and other improvements in quality of life.